Chemokine-Ligands/Receptors: Multiplayers in Traumatic Spinal Cord Injury - Friederike Knerlich-Lukoschus; Janka Held-Feindt (Hindawi Limited, 2015)
Spinal cord injury (SCI) results in complex posttraumatic sequelae affecting the whole neuraxis. Due to its involvement in varied neuromodulatory processes, the chemokine-ligand/receptor-network is a key element of secondary lesion cascades induced by SCI. This review will provide a synopsis of chemokine-ligand/receptor-expression along the whole neuraxis after traumatic spinal cord (sc) insults on basis of recent in vivo and in vitro findings in a SCI paradigm of thoracic force-defined impact lesions (Infinite Horizon Impactor) in adult rats. Analyses of chemokine-ligand/receptor-expression at defined time points after sc lesion of different severity grades or sham operation revealed that these inflammatory mediators are induced in distinct anatomical sc regions and in thalamic nuclei, periaqueductal grey, and hippocampal structures in the brain. Cellular and anatomical expression profiles together with colocalization/expression of neural stem/progenitor cell markers in adult sc stem cells niches or with pain-related receptors and mediators in dorsal horns, dorsal columns, and pain-processing brain areas support the notion that chemokines are involved in distinct cascades underlying clinical posttraumatic impairments and syndromes. These aspects and their implication in concepts of tailored SCI treatment are reviewed in the context of the recent literature on chemokine-ligand/receptor involvement in complex secondary lesion cascades.